2011
DOI: 10.1111/j.1540-8167.2011.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Arrhythmias Arising from the Right Ventricular Septum Close to the His Bundle: Features of the Local Electrogram at the Optimal Ablation Site

Abstract: The successful ablation site of the para-Hisian VAs had distinctive local electrogram characteristics. A longer R-wave duration of the bipolar electrogram with high-frequency potentials could be a novel predictor of a successful ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
(49 reference statements)
2
20
1
Order By: Relevance
“…As they reported previously, they found that moderator band PVCs had a later precordial transition (>V4) . They confirmed previous reports that para‐Hisian PVCs had shorter QRS durations and papillary muscle and moderator band PVCs had wider QRS complexes and more notching in the inferior leads …”
supporting
confidence: 89%
See 1 more Smart Citation
“…As they reported previously, they found that moderator band PVCs had a later precordial transition (>V4) . They confirmed previous reports that para‐Hisian PVCs had shorter QRS durations and papillary muscle and moderator band PVCs had wider QRS complexes and more notching in the inferior leads …”
supporting
confidence: 89%
“…Interestingly, prior reports of anterolateral papillary muscle ventricular arrhythmias have not shown ILD . Similarly, previous studies of moderator band and para‐Hisian PVCs have rarely shown ILD …”
mentioning
confidence: 83%
“…Para-Hisian electro grams at successful ablation sites sometimes show a relatively long R wave duration with high-frequency ventricular potentials compared with discrete and narrow electrograms in patients whose arrhythmias originate from other RVOT sites. 75 Complications from ablating in the para-Hisian region include atrioventricular block or right bundle branch block. Therefore, ablation should be avoided if a bundle of His potential >0.1 mV is recorded on the distal bipolar electrogram of the ablation catheter.…”
Section: Annular Ventricular Tachycardiamentioning
confidence: 99%
“…Most occur in the septal region and are classified as para-Hisian, whereas the remainder originate circumferentially from the tricuspid annulus, including the posterior, lateral, and anterior regions. [74][75][76] Electrocardiographic findings in this type of arrhythmia can be understood by considering its rightward and inferior anatomical position relative to the RVOT. Therefore, characteristic findings include an R or r wave in leads I and aVL, and an R-wave amplitude in lead II that is greater than that in lead III (Figure 4).…”
Section: Annular Ventricular Tachycardiamentioning
confidence: 99%
“…ECG criteria are useful for localizing these arrhythmias and are categorized into general patterns . As expected, based on the His bundle's anatomic relationship to the RVOT, being relatively rightward, inferior, and septal, para‐Hisian VT inscribes an R wave in lead aVL.…”
Section: Tricuspid Annular Vtmentioning
confidence: 97%